Synapse alterations in autism: Review of animal model findings - Zaťková, Marta; Bakoš, Ján; Hodosy, Július; Ostatníková, Daniela (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2016)
BACKGROUND: Recent research has produced an explosion of experimental data on the complex neurobiological mechanisms of developmental disorders including autism. Animal models are one approach to studying the phenotypic features and molecular basis of autism. In this review, we describe progress in understanding synaptogenesis and alterations to this process with special emphasis on the cell adhesion molecules and scaffolding proteins implicated in autism. Genetic mouse model experiments are discussed in relation to alterations to selected synaptic proteins and consequent behavioral deficits measured in animal experiments. METHODS: Pubmed databases were used to search for original and review articles on animal and human clinical studies on autism. RESULTS: The cell adhesion molecules, neurexin, neurolignin and the Shank family of proteins are important molecular targets associated with autism. CONCLUSION: The heterogeneity of the autism spectrum of disorders limits interpretation of information acquired from any single animal model or animal test. We showed synapse-specific/ model-specific defects associated with a given genotype in these models. Characterization of mouse models with genetic variations may help study the mechanisms of autism in humans. However, it will be necessary to apply new analytic paradigms in using genetically modified mice for understanding autism etiology in humans. Further studies are needed to create animal models with mutations that match the molecular and neural bases of autism.
Keywords: Autistic Disorder; Synapses; myši; autistická porucha; Disease Models, Animal; modely nemocí na zvířatech; Nerve Tissue Proteins; Cell Adhesion Molecules; zvířata; Humans; Mice; synapse; molekuly buněčné adheze; proteiny nervové tkáně; lidé; Animals